Imaging in pleural mesothelioma: A review of the 13th International Conference of the International Mesothelioma Interest Group. (November 2016) - Armato, Samuel G.; Blyth, Kevin G.; Keating, Jane J.; Katz, Sharyn; Tsim, Selina; Coolen, Johan; Gudmundsson, Eyjolfur; Opitz, Isabelle; Nowak, Anna K.
Highlights: Intraoperative optical imaging helps evaluate resection completeness. Contrast-enhancement in MRI may provide additional information based on time delay. DWI-based tumor volume and histogram features are related to patient survival. Dynamic contrast-enhanced CT may capture mesothelioma tumor physiologic changes. CT-based tumor volume is only moderately correlated with surgical specimen weight. Abstract: Imaging plays an important role in the detection, diagnosis, staging, response assessment, and surveillance of malignant pleural mesothelioma. The etiology, biology, and growth pattern of mesothelioma present unique challenges for each modality used to capture various aspects of this disease. Clinical implementation of imaging techniques and information derived from images continue to evolve based on active research in this field worldwide. This paper summarizes the imaging-based research presented orally at the 2016 International Conference of the International Mesothelioma Interest Group (iMig) in Birmingham, United Kingdom, held May 1–4, 2016. Presented topics included intraoperative near-infrared imaging of mesothelioma to aid the assessment of resection completeness, an evaluation of tumor enhancement improvement with increased time delay between contrast injection and image acquisition in standard clinical magnetic resonance imaging (MRI) scans, the potential of early contrast enhancement analysis to provide MRI with a role in mesothelioma detection, the differentiation of short- and long-term survivors based on MRI tumor volume and histogram analysis, the response-assessment potential of hemodynamic parameters derived from dynamic contrast-enhanced computed tomography (DCE-CT) scans, the correlation of CT-based tumor volume with post-surgical tumor specimen weight, and consideration of the need to update the mesothelioma tumor response assessment paradigm.